Effects of Aggregate Abrasrion Values to Marshall Properties of Asphalt Concrete AC- WC - Tarigan, Gunawan; Husni Malik Hasibuan, Muhammad; Lubis, Marwan; Tanjung, Darlina; Sarifah, Jupriah; Hasibuan, Abdurrozzaq; Dwi Putri, Lusi (International Journal of Engineering and Technology, 2018)
Asphalt Concrete AC-WC is one of the most common pavement types used in Indonesia, consisting of a mixture of hard asphalt, filler and a continuous graded aggregate, which is mixed, pave and compacted at a certain temperature. The mixture of ashpalt concrete requires a mixing process that uses materials as the specifications. Aggregate abrasion becomes an important part that will be examined based on aggregate hardness each of quarry. Source of material are from Selayang, Sibiru-biru and Armed. Reference for properties value that use in this study is specificationÂ  from Public Works Department in 2005. From the Experimental, abrasion of material from Selayang 13.51%, Sibiru-biru 17.08% and Armed 35.64%. Optimum Asphalt content was 5.2%, 5.7% and 6.2%. From the research, the results of abrasion testing in this study, the coarse aggregate derived from the three quarry can be used as an aggregate mixture on (AC-WC), with abrasion value < 40%, and mixed properties (stability, flow, VMA , VIM, VFA, MQ) meet the standard specifications of the Department of Public Works April 2005. Increase value of abrasion will decrease performance of asphalt concrete. One of indicator is stability value, in this study the maximum stability value is 1005.31 kg at abrasion value of 13.51%. Increase value of abrasion also decrease the durability, maximum residual stability is 915.73 kg and durability is 91.09%.Â Â
Keywords: Abrasion; Aggregate; Marshall Properties